Bis(benzoyl) phosphate inactivators of beta-lactamase C from Mtb. Issue 16 (15th August 2019) - White, Dawanna S.; Choy, Cindy J.; Moural, Timothy W.; Martin, Stacy E.; Wang, Jing; Gargaro, Samantha; Kang, ChulHee; Berkman, Clifford E.
Graphical abstract: Abstract: The class A β-lactamase BlaC is a cell surface expressed serine hydrolase of Mycobacterium tuberculosis ( Mtb ), one of the causative agents for Tuberculosis in humans. Mtb has demonstrated increased susceptibility to β-lactam antibiotics upon inactivation of BlaC; thus, making BlaC a rational enzyme target for therapeutic agents. Herein, we present the synthesis and structure-activity-relationship data for the 1st-generation library of bis(benzoyl) phosphates (1 –10 ). Substituent effects ranged from σp  = −0.27 to 0.78 for electronic and π = −0.41 to 1.98 for hydrophobic parameters. Compounds 1, 4 and 5 demonstrated the greatest inhibitory potency against BlaC in a time-dependent manner (kobs  = 0.212, 0.324, and 0.450 mn −1 respectively). Combined crystal structure data and mass spectrometric analysis of a tryptic digest for BlaC inactivated with 4 provided evidence that the mechanism of inactivation by this bis(benzoyl) phosphate scaffold occurs via phosphorylation of the active-site Ser-70, ultimately leading to an aged form of the enzyme.